2015
DOI: 10.1186/s13049-015-0136-9
|View full text |Cite
|
Sign up to set email alerts
|

Airway management by physician-staffed Helicopter Emergency Medical Services – a prospective, multicentre, observational study of 2,327 patients

Abstract: BackgroundDespite numerous studies on prehospital airway management, results are difficult to compare due to inconsistent or heterogeneous data. The objective of this study was to assess advanced airway management from international physician-staffed helicopter emergency medical services.MethodsWe collected airway data from 21 helicopter emergency medical services in Australia, England, Finland, Hungary, Norway and Switzerland over a 12-month period. A uniform Utstein-style airway template was used for collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
70
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 26 publications
12
70
2
Order By: Relevance
“…Nevertheless, the likelihood of difficult intubation outside the hospital is considerably high and considered to be around 13% (21). In our trial, first attempt direct laryngoscopy intubation also failed in 13.9% (22/158), which is comparable with some 14.5% observed in an international multicenter observational study (22). We speculate that two main reasons may account for this observation: first, the airway providers proficiency; and second, typical prehospital airway management problems, such as unexpected anatomic findings, blood or fluids in the upper airway, and specific environmental issues (4).…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, the likelihood of difficult intubation outside the hospital is considerably high and considered to be around 13% (21). In our trial, first attempt direct laryngoscopy intubation also failed in 13.9% (22/158), which is comparable with some 14.5% observed in an international multicenter observational study (22). We speculate that two main reasons may account for this observation: first, the airway providers proficiency; and second, typical prehospital airway management problems, such as unexpected anatomic findings, blood or fluids in the upper airway, and specific environmental issues (4).…”
Section: Discussionsupporting
confidence: 89%
“…Recently, the Airport study reported the results of 2327 out-ofhospital intubations in several European HEMS. 26 Interestingly, this particular study reported similar findings as the current study regarding the overall incidence of patients requiring advanced airway management (16% vs. 16.1% in our study), a higher number of male patients (72% vs. 75%), and the percentage of patients undergoing tracheal intubation (92% vs. 94.4%). However, first attempt tracheal intubation was successful only in about 85.5%, compared to 96.4% in our study, whereas the overall success rate was 98.8% compared to 99.5% in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Again, these differences might also be due to the different level of experience of the anaesthesia providers as the level of experience ranged between 0 and more than 1000 previous intubations in the Airport study. 26 Another very recent study from an Australian HEMS also reported successful intubations during the first laryngoscopy in only 372 out of 443 patients (84%). 27 However, 65.5% of these attempted intubations were performed by paramedics and the authors subsequently reported an odds ratio of 3.23 (95% confidence interval 1.67-6.52) for the need of more than one intubation attempt when the intubation was conducted by a paramedic.…”
Section: Discussionmentioning
confidence: 94%
“…63 Airway management in the prehospital setting continues to be an important area of investigation, with recent data suggesting that although overall success rates are high, first-attempt failure rates are noted to be higher in patients with cardiac arrest compared with those without cardiac arrest. 64 Endotracheal intubation is associated with improved outcomes compared with the use of supraglottic airway devices. 6 The initiation of therapeutic hypothermia in the field is not more effective than induction after hospital arrival.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%